On the Prepuna biogeographic province: A nomenclatural clarification - Morrone, Juan J.; Ezcurra, Cecilia (Zootaxa, 2016)
The nomenclatural status of the Prepuna province sensu Cabrera (1951) and sensu Morrone (1999) is clarified. The Prepuna province sensu Cabrera (1951) is demoted to a district of the Monte province, stat. nov. The valid name of the Prepuna province sensu Morrone (1999) is Cuyan High Andean province Cabrera, 1971, stat. nov. Diagnoses of these areas are provided and their endemic taxa are listed.